Existence Results for Fractional Integrodifferential Equations of Sobolev Type with Deviating Arguments - Kamalapriya, B.; Balachandran, K.; Annapoorani, N. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we establish the existence of solutions of fractional integrodifferential equations of Sobolev type with deviating arguments. The solution representation is given by the resolvent operators and the existence is proved using the fixed point theorem. An example is provided to illustrate the theory.